Media in maintaining peace as a legitimate order in Tajikistan - Салимов, Диловар (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2023)
. The article discusses the importance of the media in the context of the implementation of the peacekeeping policy as a legitimate order in modern Tajikistan. The communication factors of the stability of the peacekeeping policy as a legitimate order are revealed, which simultaneously acts as the basis for the stability of the current political regime in the conditions of political and ideological confrontation before and after the civil war. The pluralism of interpretation of the world as a legitimate order is described. This aspect is considered in a comparative manner in the context of the analysis of the works of Tajik and Western researchers. The author comes to the conclusion that in post-conflict Tajikistan, the justification of the regime’s policy becomes an important factor, whose stability suggests the existence of mechanisms for the information impact of the authorities on society and models of political positioning of the media. One likely outcome of this model was the narrowing of the space for public challenge, which in turn made it much more difficult for mechanisms to ensure the validity of regime policies. The presence of such a media strategy in the country led, on the one hand, to a change in the political positioning of the media, on the other hand, to the use by the authorities of all favorable opportunities for solving existing problems, an example of which is the formation of a policy of maintaining peace as a legitimate order in the post-conflict period.